Labyrinths of exemplarity : at the limits of deconstruction - Harvey, Irene E., 1953- (SUNY series in contemporary continental philosophy., 2002)
"Labyrinths of Exemplarity presents the first comprehensive, in-depth study of the problem of exemplarity - or how we move between the general and the particular in order to try to understand our world. The author's focus ranges from the most basic and fundamental issues of what examples are and where they come from to the complex key issues of how examples function in the discourses they inhabit and what this functioning tells us about the nature of examples or exemplarity itself. The problem is treated especially in connection to Rousseau and Aristotle, with reference to deconstruction (especially Derrida) and the range of Western metaphysics. Ultimately, a new theory of examples is offered, one not drawn from the assumptions made by earlier philosophers but rather from the usage and functioning of examples in philosophical discourse."--Jacket